Compensatory education: an analysis of a phenomenon: implications for future policies - Van Papendorp, Jennifer (School of Education, 2025)
This study focuses on the phenomenon of compensatory education in postapartheid South Africa. Compensatory education programmes have been initiated by civil society in an attempt to bridge the gap in academic achievements between pupils from advantaged and disadvantaged backgrounds. Influenced by the "human capital" theory, many of these programmes have been sponsored by business as part of their social responsibility programmes, in an effort to create a more skilled and productive work force. Targeting high school pupils, these programmes have tended to emphasise Mathematics and Science subjects The major concern of this research was to investigate .. whether compensatory education programmes were effective in contributing towards bridging the educational gap between pupils from disparate backgrounds whether compensatory education programmes continued to be relevant for the post-apartheid South African youth in a rapidly changing, transforming and globalizing society. A brief review of the causes of the educational backlog in South Africa and a history of the emergence of this particular intervention provided the background to the study. As one form of educational intervention, it was necessary to contextualize compensatory education within the education reform debate, to understand the ideologies and assumptions that underpin the intentions, and the theories that have informed the practices. A review of the international literature in the field furnished an overview of the issues involved and the strengths and weaknesses that have been documented world-wide. A constructivist methodology was used to build a case study of one particular compensatory programme, the Engen Educational Programme, which was iii subsequently subjected to comparisons with other local programmes in an effort to elicit generalised findings about this phenomenon. The findings may be summarised as follows: Quantitative assessments of enhanced academic achievement were inconclusive while qualitative responses indicated that pupils believed that they were being helped. While the programmes may have been of supplementary assistance to those pupils who already embrace a learning culture, the pupils who are most at risk lack the basic skills and language proficiency in English to cope with the Scientific subjects and many lack the staying power to benefit from this type of intervention, in its current form. The teaching approach replicates that of the school, using out-of-date teaching methods to "give" pupils information. Scant attention has been paid to guiding pupils to become self-sufficient learners who are able to engage with the material and become resourceful, skilled workers who could cope with change. Conclusions from this study are that educational interventions supported by business and civil society are still relevant in post-apartheid South Africa. However, sponsors and management of these interventions need to learn from the experiences elsewhere in the world and institute processes of on-going evaluation to ensure that programmes are effective and that valuable resources are not being wasted. Strategies emerging from this study that need to be considered are; the fostering of efficient delivery through improved organisation; the clarification of aims and achievable goals; the development of efficient internal and external evaluative procedures; the instituting of specialised tutor training and the identification of teaching approaches, different from regular schooling, that will excite a culture of learning, ensure pupil commitment and continuity and better prepare pupils for work and for responding to, coping with and even inspiring positive change. iii subsequently subjected to comparisons with other local programmes in an effort to elicit generalised findings about this phenomenon. The findings may be summarised as follows: Quantitative assessments of enhanced academic achievement were inconclusive while qualitative responses indicated that pupils believed that they were being helped. While the programmes may have been of supplementary assistance to those pupils who already embrace a learning culture, the pupils who are most risk lack the basic skills and language proficiency in English to cope with the Scientific subjects and many lack the staying power to benefit from this type of intervention, in its current form. The teaching approach replicates that of the school, using out-of-date teaching methods to "give" pupils information. Scant attention has been paid to guiding pupils to become self-sufficient learners who are able to engage with the material and become resourceful, skilled workers who could cope with change. Conclusions from this study are that educational interventions supported by business and civil society are still relevant in post-apartheid South Africa. However, sponsors and management of these interventions need to learn from the experiences elsewhere in the world and institute processes of on-going evaluation to ensure that programmes are effective and that valuable resources are not being wasted. Strategies emerging from this study that need to be considered are; the fostering of efficient delivery through improved organisation; the clarification of aims and achievable goals; the development of efficient internal and external evaluative procedures; the instituting of specialised tutor training and the identification of teaching approaches, different from regular schooling, that will excite a culture of learning, ensure pupil commitment and continuity and better prepare pupils for wo